Elastomers - Cankaya, Nevin (IntechOpen, 2017)
Summary-Book Contents: Your purpose of reading this book is to concentrate on recent developments on elastomers. The articles collected in this book are contributions by invited researchers with a long-standing experience in different research areas. I hope that the material presented here is understandable to a broad audience, not only scientists but also people with many different disciplines. The book contains eleven chapters in two sections: (1) "Mechanical Properties of Elastomers" and (2) "Elastomers for Natural and Medical Applications." The book provides detailed and current reviews in these different areas written by experts in their respective fields. This book will be useful for polymer workers and other scientists alike and will contribute to the training of current and future researchers, academics, PhD students, and other scientists.